Multicenter, randomized comparison of the diagnostic accuracy of 19-gauge stainless steel and nitinol-based needles for endoscopic ultrasound-guided fine-needle biopsy of solid pancreatic masses. Issue 3 (April 2020) - Hann, Alexander; Epp, Sonja; Veits, Lothar; Rosien, Ulrich; Siegel, Julian; Möschler, Oliver; Bohle, Wolfram; Meining, Alexander
Background: The use of 19-gauge (G) stainless steel needles for endoscopic ultrasound-guided fine-needle biopsy of a pancreatic mass often results in technical difficulties due to an inability to advance the relatively rigid needle out of the endoscope. More flexible nitinol-based needles might decrease such technical difficulties and thus increase diagnostic accuracy. Objective: In this prospective multicenter randomized single-blinded study we compared the diagnostic value of those two needle types in patients with a solid pancreatic lesion. Methods: Patients with a solid pancreatic mass were diagnosed with endoscopic ultrasound-guided fine-needle biopsy using one puncture with each needle in a randomized fashion. The primary endpoint was the diagnostic accuracy of each needle. Secondary endpoints included time for puncture, amount of tumour tissue obtained, and technical failure. Histological specimens were centrally reviewed by a pathologist blinded to the final needle type and final diagnosis (ClinicalTrials.gov Identifier: NCT02909530). Results: Out of 46 prospectively recruited patients, central pathological examination was available for 41. Diagnostic accuracy for the two needles combined was 87.8%. Diagnostic accuracy was 66% and 68% using the stainless steel- and nitinol-based needle respectively. Time spent for puncturing was 137 ± 61 s (mean ± standard deviation) for the stainless steel and 111 ± 53 s for the nitinol-based needle ( p = 0.037). Technical failure occurred in three (6.5%) cases using the stainless steel- and in none using the nitinol-based needle. Conclusions: Usage of a nitinol-based 19-G needle failed to present a significant superior accuracy compared with a stainless steel needle in endoscopic ultrasound-guided fine-needle biopsy of solid pancreatic lesions.